EFFICACY OF DHATHU BUSHTI CHOORANAM IN THE MANAGEMENT OF MALE INFERTILITY WITH SPECIAL REFERENCE TO OLIGOSPERMIA - AN OPEN PILOT STUDY (International Journal of Ayurveda and Pharma Research, 2018)
Infertility is a common problem of new age couples. It is affecting them psychologically and also affecting the harmony of the family. Among infertility couples, 40% was caused by male partner particularly by oligospermia. Literally oligospermia means insufficient number of spermatozoa in semen, but significantly, it means that oligospermia is a medical condition characterized by the total sperm count less than 20 million/ml of ejaculate. Extensive clinical researches are going on worldwide to treat oligospermia by utilizing various natural sources like plants, mineral and animal origin.Siddha medicine is having many formulations to treat oligospermia, one among them is Dhathu bushti chooranam described in Noigalukku Siddha Parigaram –a Sasthiric siddha literature. 10 male partners of infertility couples attending Sool mahalir maruthuvam OPD of the Ayothidoss Pandithar Hospital, National Institute of Siddha, Tambaram sanatorium, Chennai-47 were recruited for this pilot study. All patients were treated with 10 gm of Dhathu bushti chooranam twice a day with milk for 90 days. All patients were subjected to complete semenogram on 0th and 90th day of treatment. Results were observed by analyzing the semenogram parameters. The ingredients of Dhathu bushti chooranam are Salamisiri, Nilapanai kizhangu,Thaneervittan kizhangu, Poonaikaali vidhai, Boomisarkkarai kizhangu and most of them are having good spermatogenesis and aphrodiasic activities, hence the author selected this drug for this study. The efficacy of the trial drug Dhathu bushti chooranam was appreciable and the drug may be taken for clinical trial in large number of population.